Reevaluation of Land Fitness For Soybean Plant in Kabamatan Stabat, Langkat District - Leni Handayani; A Rauf; Rahmawaty Rahmawaty; T Supriana (International Journal of Applied Biology, 2020)
A decrease in the area of soybean farming has an effect on reducing soybean production from year to year so that it has not been able to meet the needs of national soybean consumption. Land suitability assessment is an effort to be able to optimize land use. In the process of assessing land suitability manually, it is considered inaccurate. The purpose of this study was to determine the land suitability class for soybean plants. The land suitability classification system used is the FAO land suitability classification classified at the sub-class level. Land suitability evaluation uses a matching system, as well as comparing the characteristics of land with plant growing community formulated in the technical evaluation of land guidelines for agricultural commodities. In the matching process Leibig's minimum law is used to determine the limiting factors that will affect the suitability of the class and sub-class of the land. Requirements for growing plants become kiteria in conformity evaluation. The results showed that the limiting factors of land suitability for soybean plants that had to be improved were temperature, rainfall, soil texture, C-Organic, N-Total and P-Available soil. The limiting factor of temperature and soil texture cannot be improved so that the marginal fit class (S3) on actual land suitability remains marginal fit (S3) in terms of potential land suitability.